2020
DOI: 10.1016/j.heliyon.2020.e04625
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) vaccine status and knowledge of students at a university in rural Thailand

Abstract: Background Human papillomavirus (HPV) is a sexually transmitted virus that causes cancers of the cervix, anus, vagina, penis, and oropharynx. HPV vaccination prevents HPV types that commonly cause these cancers. HPV vaccines have been approved in Thailand since 2007. However, the vaccination rate remains low, particularly in young people. Objectives This study aimed to investigate the information level regarding HPV infection and vaccination in the younger Thai populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 17 publications
0
21
1
6
Order By: Relevance
“…Meanwhile, in Thailand, the HPV vaccination program involves males aged 13–21 years besides females aged 9–26 years. Indeed, catch up vaccination to age 26 is suggested for men who have sex with men (MSM), transgender people, and immunocompromised persons [ 91 ]…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in Thailand, the HPV vaccination program involves males aged 13–21 years besides females aged 9–26 years. Indeed, catch up vaccination to age 26 is suggested for men who have sex with men (MSM), transgender people, and immunocompromised persons [ 91 ]…”
Section: Discussionmentioning
confidence: 99%
“…A self-reported study in Thailand revealed that only 1.9% of 521 undergraduate students had a history of vaccination. (Chanprasertpinyo and Rerkswattavorn, 2020). The reasons to decline vaccination were two-fold: the expenses of the vaccine and the lack of awareness of HPV infection (Ratanasiripong Nop et al, 2018;Chanprasertpinyo and Rerkswattavorn, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…16 17 22 23 The respondents' awareness and knowledge of HPV infection was also far below par compared with other highincome or low-income countries. [24][25][26][27] More than half of the students (51.8%) were unaware that HPV infection could cause genital warts. This rate was high as compared with other high-income or low-income countries.…”
Section: Open Accessmentioning
confidence: 99%